2003
DOI: 10.1152/jn.00475.2003
|View full text |Cite
|
Sign up to set email alerts
|

Beta and Gamma Oscillations in the Olfactory System of the Urethane-Anesthetized Rat

Abstract: . Beta and gamma oscillations in the olfactory system of the urethane-anesthetized rat. J Neurophysiol 90: 3921-3930, 2003. First published August 13, 2003 10.1152/jn.00475.2003. Fast oscillations in the beta (15-40 Hz in awake rats) and gamma (50 -100 Hz) frequency ranges are prominent in field potentials induced by odorants in the mammalian olfactory bulb (OB) and piriform cortex (PC). Whereas the gamma oscillation has been studied for Ͼ50 yr, the beta oscillation has attracted attention only recently, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
270
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(293 citation statements)
references
References 43 publications
21
270
2
Order By: Relevance
“…Recently, a current source density analysis revealed that the granule cell dipoles provide large current flows during ␥ oscillations (Neville and Haberly, 2003). In line with this, we found that the major part of the currents leading to LFP oscillations came from the EPL, near the MCL, with an inversion below the MCL (Fig.…”
Section: Nature Of Field ␥ Oscillationssupporting
confidence: 85%
See 2 more Smart Citations
“…Recently, a current source density analysis revealed that the granule cell dipoles provide large current flows during ␥ oscillations (Neville and Haberly, 2003). In line with this, we found that the major part of the currents leading to LFP oscillations came from the EPL, near the MCL, with an inversion below the MCL (Fig.…”
Section: Nature Of Field ␥ Oscillationssupporting
confidence: 85%
“…Previous theoretical investigations have suggested that granule cells, the largest population of bulbar interneurons, constitute the main generators of extracellular current flows (Rall and Shepherd, 1968;Freeman, 1975), but in vivo data supporting this assumption came out only recently (Neville and Haberly, 2003). The relative contribution of granule cells and bulbar output neurons (i.e., mitral/tufted cells) implicated in fast oscillations still remains speculative, although a phase relationship between mitral/tufted cell spiking activity and LFP oscillations has been found (Kashiwadani et al, 1999;Buonviso et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also measured the local field potential (LFP) from the mitral cell layer, which allowed us to record subthreshold activity from both mitral and granule cells (39). At rest, with the nostril open, breathing induced theta-frequency deflections, and odors elicited gamma oscillations (Fig.…”
Section: S2dmentioning
confidence: 99%
“…In the OB, the LFP signals in different frequencies (Fig. 1A) have different origins, amplitudes, and functions (22)(23)(24)(25). The GCL contains a large amount of local neurons whose dendrites radiate almost exclusively toward the more superficial external plexiform layer, generating the strongest LFP signals in the OB (24,25).…”
mentioning
confidence: 99%